2010
DOI: 10.1029/2010gl043133
|View full text |Cite
|
Sign up to set email alerts
|

Major shifts in multidecadal moisture variability in the Mid‐Atlantic region during the last 240 years

Abstract: The paucity of high‐resolution paleoclimate records limits our ability to extend instrumental data into a longer time‐frame and to better understand multidecadal climate variations in the Mid‐Atlantic region. Here we present an ∼2 year‐resolution endogenic calcite δ18O record for the last ∼240 years from a freeze core at White Lake in northern New Jersey. The δ18O data, consistent with the paleosalinity reconstructions from Chesapeake Bay, suggest regional‐scale multidecadal moisture variations, including dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…For example, Grimaldi (2008) discovered that during the El Niño (warm) phase of the El Niño-Southern Oscillation (ENSO), early winter months in Syracuse are generally warmer, with anomalously low snowfall totals. For example, Zhao et al (2010) suggested that changes in the AMO result in shifts in the magnitude and location of the jet stream. Also, during El Niño years major snow events are 5 times as likely to occur in Syracuse.…”
Section: Potential Factors Of Snowfall Variabilitymentioning
confidence: 99%
“…For example, Grimaldi (2008) discovered that during the El Niño (warm) phase of the El Niño-Southern Oscillation (ENSO), early winter months in Syracuse are generally warmer, with anomalously low snowfall totals. For example, Zhao et al (2010) suggested that changes in the AMO result in shifts in the magnitude and location of the jet stream. Also, during El Niño years major snow events are 5 times as likely to occur in Syracuse.…”
Section: Potential Factors Of Snowfall Variabilitymentioning
confidence: 99%
“…The abrupt rise of small Discostella percentages during the AD 1860s that is represented in the Wolf-62 core was apparently not accompanied by unusually abrupt shifts in regional lake levels, temperatures, or ice cover (Stager and Thill, 2010; Wilcox et al, 2007; Zhao et al, 2010). The increase in Discostella abundances might instead be related to nutrient enrichment from human activity in the watershed, as has been documented for D. stelligera in Walden Pond, Massachusetts (Köster et al, 2005).…”
Section: Discussionmentioning
confidence: 94%